Exploring the Musical Mind: Cognition, Emotion, Ability, Function - Sloboda, John A. (Oxford Oxford University Press, 2005)
In the 20 years since publication of John Sloboda's landmark volume The Musical Mind, music psychology has developed as a vibrant area of research - exerting influence on areas as diverse as music education and cognitive neuroscience. This new book brings together 24 selected essays and reviews written by an internationally acclaimed authority on music and the mind. Chapters are grouped into four main areas of study. These are, cognitive processes (including music reading, memory and performance), emotion and motivation, talent and skill development, and music in the real world (including functions of music in everyday life and culture). The book ends with a newly written chapter on music psychology and social benefits. The books brings together in one place a range of influential writings, whose links to one another provide a compendious overview of a subject that has come to maturity during the author's career, a career which has significantly contributed to the development of the field.
Keywords: Music psychology